Restorative justice principles: A leadership framework to de-escalate unrests in South African higher educational institutions - Adewale, S.; Ndwandwe, N. D. (South African Journal of Higher Education, 2025)
The persistent unrest in South African higher education highlights the pressing need for an innovative approach to conflict resolution. This conceptual article explores restorative justice as a leadership framework to overcome this societal menace. Traditional approaches to managing unrest have proven insufficient to address the root causes of conflict. This article adopts a conceptual research design of a theory synthesis approach within the transformative paradigm. This involves reviewing, analysing, and conceptualising the integration of existing concepts and theories or literature streams. Restorative justice grounded in the value of empathy, accountability, and collaboration offers a transformative approach to promoting a culture of trust and mutual respect. This article emphasises the essential role of education leaders in championing this framework, emphasising strategies such as articulating a shared vision, providing professional development, creating supportive structures and modelling restorative practices. It is concluded that leaders who embrace restorative justice principles can de-escalate conflicts, enhance relationships and promote social cohesion.